Future is no problem for IT. (Times Higher Education Supplement, 1999)
Announces that student programmers from Canada have won the ACM International Collegiate Programming World Finals in Eindhoven, Holland in 1999. Number of problems given to contestants; Information on the teams that made it to the finals; Results of a survey made by IBM on students' job preferences and attitudes.